Teachers’ Perspective on Implementation of the Double Track Senior High School System in Ghana - Mensah, Dominic Kwaku Danso (International Journal of Emerging Trends in Social Sciences, 2019)
The study sought to explore teacher’ perspective on the implementation of the double track senior high school education system in Ghana; specifically, in the Effutu Municipality and Gomoa East Districts of Ghana. The study employed sequential exploratory design. Semi structured interviews and structured questionnaires were used to gather data for the study. The population comprised head teachers and teachers. The purposive and simple random sampling procedures were used to select head teachers and teachers respectively. The sample size of the study was 95 which comprise five (5) head teachers and ninety (90) teachers within the Effutu municipality and Gomoa East Districts of the Central Region of Ghana. Majority of the respondents perceived that the implementation of the double track senior high school system in their school has resulted in increased enrollment, reduced class sizes, and increased contact hours, recruitment of new teachers and optimal use of school facilities. Challenges confronting the implementation of the double track senior high school system in the study area were inadequate stakeholder consultation, inadequate provision of logistics and funds by the government, quality of education being compromised, possible incompletion of syllabus owing to increased number of holidays and maintenance of school facilities becoming a problem. The study, therefore, recommends that policy makers (Ministry of Education and Ghana Education Service) should strategically involve head teachers and teachers in the development of policies since the teachers are the key implementers of the policy. Government should also ensure adequate provision of resources and logistics for successful implementation of its policies.